PENGUKURAN KADAR LOGAM Hg, KADMIUM, ARSEN, DAN KROMIUM (VALENSI 6) DALAM AIR SUMUR - Ngibad, Khoirul (UIN AR-RANIRY, 2023)
The presence of metals such as Hg, Cd, As, and Cr6+ in waters can cause health problems. Hg poisoning causes central nervous system symptoms, Cd poisoning can cause digestive problems and kidney disease, As poisoning can cause jaundice, kidney bleeding, and skin cancer and Cr6+ is highly corrosive and can cause cancer. This study aimed to measure the levels of Hg, Cd, As, and Cr6+ in water wells in Taman District, Sidoarjo Regency. In this study, the AAS method was used at 253.7 nm for Hg analysis; 228.8 nm for Cd analysis; 193.7 nm on As analysis, and UV-Vis spectrophotometric method at 530/540 nm for Cr(VI) analysis. The water wells in Taman District, Sidoarjo Regency have Hg, As, Cd, and Cr6+ levels of 0.0006 each; <0.002; <0.0002; and <0.013 mg/L (well water A) and <0.0006; <0.002; <0.0002; and <0.013 mg/L (well water B). Based on the chemical parameters, it can be concluded that the levels of Hg, As, Cd, and Cr6+ still meet the quality standards (maximum levels).